Pemanfaatan Sekam Padi dan Kulit Batang Sagu terhadap Mutu Briket dengan Perekat Tapioka - Yasa Rudin; Raswen Efendi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Briquette is a biomass fuel. Biomass has the potential and benefits of being an alternative energy source to replace fossil fuels that exist today, biomass has an abundant stock or supply.The biomass used in this study was rice husk and sago steam bark. This study used a completely randomized design with a sample of four and four replications. The treatment was against the ratio of rice husk and sago bark 75:25, 50:50, 25:75, and 0: 100.). Data were statistically analyzed using anova andduncan’s new multiple range test (DNMRT) at 5% level. The results showed that the ratio of rice husk and bark significantly affected moisture, ash, density, rainfall density, fuel, and volatile material. The selected treatment in this researchrice husks and sago bark 25:75 with density of 0.500g/cm3, moisture content 5.913%, ash content 7.352%, evaporation content 2.582 %, carbon content can be used 84.152%, the heating value is 6604.630 cal/g, and the fuel power is 0.003 g/sec.  Keywords: Briquette, rice husk, sagosteam bark